XÂY DỰNG PROBE ĐỂ KHAI THÁC VÀ CHỌN GEN MÃ HOÁ ΒETA-GLUCOSIDASE GH3 TỪ DỮ LIỆU GIẢI TRÌNH TỰ DNA METAGENOME VI KHUẨN DẠ CỎ DÊ - Nguyễn, Khánh Hoàng Việt; Đỗ, Thị Huyền; Nguyễn, Hữu Đức; Vũ, Thị Ly; Trương, Nam Hải (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
PROBE DESIGN FOR EXPLOITING GENES ENCODING BETA- GLUCOSIDASE GH3 FROM DNA METAGENOME OF BACTERIA IN GOAT RUMENBeta-glucosidase enzyme belongs to family GH3 is widely used in food, medicine and pharmaceutical industries. In order to quickly search for these enzyme coding sequences from DNA metagenomic data, in this study, bacterial-derived enzyme-coding sequences which was investigated empirically on the CAZy database was collected. By analogy, we have developed that a specific probe for beta-glucosidase GH3 had a length of 330 amino acids, which contains 26 conserved residues in all sequences, 37 residues similar in almost sequences, and 21 residues conserved in many sequences and homologous with all the reference sequences with the lowest coverage and identity of 79% and 38% respectively and max score of 122. Probe was used and extracted 59 coded sequences of beta-glucosidase GH3 from the metagenome DNA sequences of goat rumen bacteria. The most ORFs were annotated as beta-glucosidase GH3 by KEGG and CAZy. The sequences are estimated to have a tertiary structure similar to beta-glucosidase.